2020
DOI: 10.13189/ujer.2020.081047
|View full text |Cite
|
Sign up to set email alerts
|

The Antecedence of Teacher's Professional Performance: Evidence from Indonesia

Abstract: Teacher professionalism determines the quality of education output. Hence, this study aims to explore the effect of good corporate governance (GCG) and knowledge management (KM) on the teacher's professional performance in Indonesia mediating by affective commitment. A questionnaire collected the research data through the survey method. The research participants are 375 teachers spreading across three provinces (Jakarta, Banten, West Java) determined by accidental sampling. Data analysis uses path analysis sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Besides, personality can be relied upon to build integrity . Other studies indicated that personality is related to job efficiency (Esfestani & Jalali, 2018) and professional performance (Mawarto et al, 2020). also claimed that personality significantly affects teacher effectiveness and burnout.…”
Section: Personality and Affective Commitmentmentioning
confidence: 95%
“…Besides, personality can be relied upon to build integrity . Other studies indicated that personality is related to job efficiency (Esfestani & Jalali, 2018) and professional performance (Mawarto et al, 2020). also claimed that personality significantly affects teacher effectiveness and burnout.…”
Section: Personality and Affective Commitmentmentioning
confidence: 95%